Sustainability & CSR: The Relationship with Hofstede Cultural Dimensions - Minoo Tehrani (MDPI AG, 2021)
This research explores the relationship between Hofstede’s femininity cultural dimension of quality of life and the masculinity cultural dimension of drive for success manifested by materialistic wealth by investigating the market value of the publicly traded firms appearing on the Dow Jones Sustainability Indices (DJSIs). The firms added to the DJSIs between the years 2010–2019 in countries with the femininity cultural dimension indicated by scores of ≤42, were selected for the first part of this study. In addition, France, with a masculinity score of 43 and Japan, with the highest masculinity score of 92, were chosen for comparison with the results from the countries with the femininity cultural dimension. The findings of this study indicate that companies in developed and emerging countries with the femininity cultural dimension show significant positive impact on their market values when added to the DJSIs. The publicly traded firms in France show a significant negative impact on their market values when added to the DJSIs. On the other hand, Japanese companies on the addition lists of DJSIs show a significant positive impact on their market values, despite Japan having the highest Hofstede masculinity score, a potential sign of cultural change in Japan.